Investigation of the role of Mediator tail subunits in antifungal drug resistance and cellular aggregation in Candida species - Lim, Wen Jun (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2025)
Candida albicans is a commensal fungal pathogen that resides on various human mucosal surfaces (e.g. oral cavity) and can cause severe infection in immunocompromised individuals. Azole antifungal resistance in C. albicans is increasing, making candidemia difficult to treat due to the lack of alternative antifungal drugs. Studies have revealed that azole resistant C. albicans isolates possess hyperactive Tac1, a transcription factor which activates expression of the efflux pump Cdr1 and ultimately confers azole resistance. Previous studies also revealed that tail components of the Mediator complex were required for Tac1-activated azole resistance in C. albicans. In this study we investigate whether the Mediator tail component Med2, encoded by the massively expanded (n=14) TLO gene family of C. albicans was required for Tac1 activity. Based on these findings, we also aimed to investigate the function of specific TLO genes, namely TLOα1 and TLOβ2, in the hyperactive Tac1-activated resistance to the antifungals fluconazole and terbinafine. To carry out this specific study, CRISPR-Cas9 was used to introduce a homozygous TAC1-5 gain-of-function point mutation into wild-type (WT), tloΔ and med3Δ strains of C. albicans which enables them to express hyperactive Tac1. qRT-PCR analysis revealed that tloΔ-TAC1-5 has reduced CDR1 expression compared to WT TAC1-5 and antifungal susceptibility testing showed that the minimal inhibitory concentration (MIC) values of fluconazole and terbinafine were decreased 2-fold. Individual copies of TLOα1 and TLOβ2 were introduced into tloΔ-TAC1-5 to investigate their role in Tac1-activated fluconazole and terbinafine resistance. qRT-PCR revealed that TLOα1 is highly expressed but TLOβ2 is weakly expressed in tloΔ TAC1-5. TLOα1 could restores the Tac1-activated fluconazole and terbinafine resistance of tloΔ TAC1-5 whereas TLOβ2 could only partially restores the Tac1-activated fluconazole resistance of tloΔ TAC1-5. Surprisingly, TLOβ2 restores the terbinafine resistance of tloΔ but reduces the terbinafine resistance of tloΔ-TAC1-5, suggesting TAC1-5 antagonized TLOβ2 expression. ChIP-qPCR was used to investigate the interaction of Tloα1 and the CDR1 promoter. These experiments revealed that Tloα1 co-localised to the drug response element (DRE) which is the site of Tac1 binding in the CDR1 promoter, whereas the interaction of Tloβ2 was much weaker. The second part of this study aimed to investigate the function of MED2 and MED15 in another multidrug resistant pathogen C. auris. CRISPR-Cas9 was used to delete MED2 and MED15 in a weakly aggregative strain 8985 and highly aggregative strain 8977. The deletion of MED2 and MED15 did not reduce the antifungal resistance of C. auris strains. However, the deletion of MED2 and MED15 increased the resistance of 8985 towards calcofluor white and congo red, suggesting cell wall changes in these mutants. The deletion of MED2 and MED15 reduced the aggregation capability of 8977 in PBS and the echinocandin induced aggregation phenotype of 8985. The deletion of MED2 and MED15 also significantly reduced the biofilm formation capability of 8977 on hydrophobic surface and in particularly on fetal bovine serum precoated surfaces. The white-opaque switching (environmental adaptation) of 8977 might also be affected by MED2 and MED15 deletion. Lastly, RNA sequencing revealed that an important aggregation-contributing adhesin, SCF1, was downregulated in the Mediator tail mutants of 8977 along with other putative adhesins and important genes. Surprisingly, the strong downregulation of a putative Als3p encoding gene B9J08_004498 might contribute to the low aggregation capability of Mediator tail mutants of 8985 despite the upregulation of SCF1. In summary, C. albicans Mediator tail protein Tloα1 is required for Tac1-activated fluconazole and terbinafine resistance whereas the corresponding Mediator tail component of C. auris, Med2 and its interacting partner Med15, regulate SCF1 and other putative adhesins required for cellular aggregation in this species.
APPROVED